Muraqqaʻ-i kālij : jis meṉ ḥālāt va rivāyāt-i Muḥammadan Kālij, ʻAlīgaṛh ke tafṣīlī darj kiʼe gaʼe haiṉ - Badruddīn, Muḥammad (SAMP early 20th-century Indian books project ;, 1916)
History of Muhammadan Anglo-Oriental College.